PEMERIKSAAN TUMBUH KEMBANG BALITA PADA MASA PANDEMIC COVID-19 DI DESA BELITAR SEBERANG, KECAMATAN SINDANG KELINGI, KABUPATEN REJANG LEBONG TAHUN 2021 - Meri Epriana Susanti; Sulastri Sulastri (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2021)
The baby refers to children aged 12 to 59 months. This is a critical time in their development. The baby's growth process has accelerated to the next level, which includes body height, body weight, lingual skill, creativity, social interaction, emotional intelligence, and intelligence. During the Covid-19 term, the government has been responsible for the service of citizens, including the baby, in terms of minimum standard service, in accordance with Ministry of Health of Indonesia regulation number 4, 2019. One of the growth assessment services is the baby's health service. The purpose of the examination of baby growth is to learn about the growth of babies in Belitar Seberang Village. This community service used participant epidemiology to assess the community problem at Belitar Sebrang Village, Sindang Kelingi Subdistrict, Rejang Lebong District, Indonesia. Body height, body weight, and the Denver II exam are the components of the baby growth assessment. The results demonstrated that the baby mother understood how to assess her child's growth. We wish the baby mother could give their time to bring their baby to the Integrated Service Center (ISC) so that their baby's growth can be assessed.